A Modified Sanford-Bennett High-H permeameter - Tenzer, R. K.; United States. Air Force. Systems Command. Aeronautical Systems Division; United States. Air Force. Systems Command. Aeronautical Systems Division. Directorate of Materials and Processes (Wright-Patterson Air Force Base, Ohio : Directorate of Materials and Processes, Aeronautical Systems Division, Air Force Systems Command, United States Air Force, 1963)
The Sanford-Bennett High-H permeameter was developed originally for measuring hysteresis loops on Alnico magnets. It permits to maintain a magnetizing force (H) of 5000 oersted (Oe) in a 5 cm gap. Some modern magnet materials of high coercive force, like barium ferrite and platinum cobalt, require much higher magnetizing forces to become saturated. Narrowing the gap is limited to 2.1 cm by the flip coil arrangement, which limits the magnetizing force to about 8000 Oe. In order to extend this limit, the permeameter had to be modified. Flip coils were replaced by a Hall probe to measure H and ''compensated coils'' to measure intrinsic induction (B-H). The minimum gap could thus be reduced to 0.65 cm and the magnetizing force increased to about 11,000 Oe. The use of tapered 40% Co 60% Fe Pole pieces and applying 200V allowed the doubling of this value. Introducing Hall probes to measure H and an ideal fluxmeter to measure (B-H) shortened measuring time to about one fourth at only a slight reduction of accuracy.
Labeled: AD0420237 (from http://www.dtic.mil).
"(Prepared under Contract No. AF33(657)-8499 by Indiana General Corporation, Valparaiso, Indiana)."
"Project No. 7371, Task No. 737103."
"May 1963."
Includes bibliographical references (page 5).
Mode of access: Internet.
Keywords: Hysteresis; Magnetic fields; Fluxmeter; Permeameter